Islet Survival and Function Following Intramuscular Autotransplantation in the Minipig. Issue 4 (15th March 2013) - Sterkers, A.; Hubert, T.; Gmyr, V.; Torres, F.; Baud, G.; Delalleau, N.; Vantyghem, M. C.; Kerr‐Conte, J.; Caiazzo, R.; Pattou, F.
<x xml:space="preserve">Abstract</x> The liver may not be an optimal site for islet transplantation due to obstacles by an instant blood‐mediated inflammatory response (IBMIR), and low revascularization of transplanted islets. Therefore, intramuscular islet transplantation (IMIT) offers an attractive alternative, based on its simplicity, enabling easier access for noninvasive graft imaging and cell explantation. In this study, we explored the outcome of autologous IMIT in the minipig (n = 30). Using the intramuscular injection technique, we demonstrated by direct histological evidence the rapid revascularization of islets autotransplanted into the gracilius muscle. Islet survival assessment was performed using immunohistochemistry staining for insulin and glucagon up to a period of 6 months. Furthermore, we showed the crucial role of minimizing mechanical trauma to the myofibers and limiting exocrine contamination. Intramuscular islet graft function after transplantation was confirmed by documenting the acute insulin response to intravenous glucose in 5/11 pancreatectomized animals. Graft function after IMIT remained however significantly lower than the function measured in 12 out of 18 minipigs who received a similar islet volume in the liver through intraportal infusion. Collectively, these results demonstrated in a clinically relevant preclinical model, suggest IMIT as a promising alternative to intraportal infusion for the transplantation of β cells in certain medical situations.